Knowledge of substance abuse among students studying in a selected higher secondary school in Biratnagar city - Subba, Neela; Subba, Dipty; Shah, Sushmita Raj (Nepalese Journal of Biosciences, 2015)
This was a cross sectional study carried out to among 115 students aged between 15-20 years of grade 12. The objective of the study was to assess the knowledge of substance abuse among students studying in selected higher secondary school of birtnagar. Students were selected by purposive sampling technique. A pretested semi structured questionnaire related to demographic and knowledge was administered and data were collected by self-administered method. The data was analyzed and interpreted by using simple descriptive and inferential statistics. Among the respondents 53% were male and 47% of them were female with the mean age of 18 years. Although, majority of respondents (51.3%) answered correctly regarding the meaning of substance, only 19.1% knew the actual meaning of substance abuse. Among them, 87.88% had good knowledge, 11.12% had average knowledge and only 2.6% had poor knowledge on over all substance abuse. The main source of information as perceived by students was peer group and media. Many of the students agreed as peer pressure (53.9%) one of the main cause for substance abuse. None of the respondents had ever taken any kinds of drugs or any other substances.